(3OhQ GdCSQI aj JQHjI GdCHfGA (B/s - (3SdjeGf, Ydjs ((3GdbGgQI (B:s (3TQcI SajQ ,s, 1994)
(3jJfGhd gPG GdcJGH ehVhY GdJfTFI GdCSQjI hhXjaJgG hOhQgG aj JQHjI GdCHfGA hjJWQb gPG GdcJGH dHYV LhGfH GdJfTFI GdGLJeGYjI eKd eUGOQgG heaghegG hOhQgG aj JNaja GdEVQGHGJ GdfaSjI(B.s
Keywords: (3GdBHGA hGdCHfGAs -- (3YdGbGJ CSQjIs; (3Yde faSs -- (3GdCWaGds